การพัฒนาปุ๋ยน้ำชีวภาพคุณภาพสูงเพื่อการปลูกข้าว: Development of High Quality Bio-fertilizer for Rice Production - Chuaynon, Chadaporn; Intanon, Pumisak (Asian Health, Science and Technology Reports, 2011)
This research aims to development of high quality of bio-fertilizers to have a high efficiency, suitability for the growth and yields of rice production. Additionally, this would help to reduce the cost of the production for the farmers. The bio-fertilizer with different materials was fermented in the 200 litres barrel according to the process of The Department of Lands Development. The experiment plan of Completely Randomized Design (CRD) was being used which included 2 trial formulas. The first formula was the formula of increasing the growth of the trunks and leaves of rice which had 5 treatments and each treatment used 1 barrel. The second formula was the formula of increasing the bearing of flowers and the weight of rice seed which also had 5 treatments and each treatment used 1 barrel. After finishing the fermentation process, the bio-fertilizer liquids were taken to analyze for the nutrients element to assess the suitability of the formulas as to find the major elements (N, P, K), the minor elements (Ca, Mg, S) and some important trace elements (Fe, Mn, Cu, Zn, B). The analyzing took place at the Faculty of Agriculture Natural Resources and Environment’s lab in Naresuan University, Phitsanulok. This was held during November and December 2009. The data were statistically analyzed by the Analysis of Variance (ANOVA), and the data were differentiated by the method of Duncan’s new Multiple Range Test (DMRT) at the confidential level 95% . In conclusion, the result shows that in the fifth treatment of the first formula of increasing the growth of the trunks and leaves of rice has the nutrient elements of N, P, Ca, Mg, Fe and S higher than any other treatments and more than general bio-fertilizers that produced by farmer . Furthermore, the fifth treatment of the second formula of increasing the bearing of flowers and the weight of rice seed has the nutrient elements of N, P, K, Ca, Fe, S and Zn higher than any other treatments and more than general biofertilizers that produced by farmer. Therefore, for planting the rice from the time of rice sprouting until the rice yielding should choose the fifth treatment in the first formula and after the rice yielding should choose the fifth treatment in the second formula as to spray throughout the rice plants for increasing the growth and also the production of the rice.